A dataset of sandstone detrital composition from Qinghai‐Tibet Plateau - Wen Lai; Xiumian Hu; Xiaolong Dong; Anlin Ma (Geoscience Data Journal, 2024)
Abstract As a hot topic in Earth sciences, the Qinghai‐Tibet Plateau has accumulated a large amount of sedimentary‐related data. We constructed a dataset of detrital components for Qinghai‐Tibet Plateau from 63 peer‐reviewed publications. The dataset thus comprises 1813 Late Proterozoic to Pleistocene sandstones from 84 stratigraphic units. For each sample, we present details on reference, detrital composition, GPS, geographic location, depositional age, tectonic setting and depositional environment. It becomes a high‐quality dataset after the information on each sandstone sample was standardized and reviewed by sedimentary experts. The dataset can be used for regional geoscience studies, exploring the general laws of the source‐to‐sink process. The dataset may also be useful in the field of utilities, such as assisting in finding suitable building stones, helping oil and gas and mineral exploration, and so forth.